Optimal Soft Composites for Under‐Actuated Soft Robots. Issue 8 (24th June 2021) - Boddeti, Narasimha; Van Truong, Tien; Joseph, Vincent S.; Stalin, Thileepan; Calais, Theo; Lee, Shien Yang; Dunn, Martin L.; Valdivia y Alvarado, Pablo
Abstract: Material properties and composite structures play key roles in tailoring the performance of soft robots. Unfortunately, current design and fabrication approaches limit achievable complexity and functionality in these two categories and hinder soft robot performance. Here, an approach that allows design and direct fabrication of novel soft composite structures is presented. The process uses computational topology optimization to determine the required 3D composite structure of soft hyper‐elastic bodies. The direct fabrication of the soft composite structures using an all‐in‐one fabrication workflow with resilient silicone polymers enables precise tailoring of mechanical properties. By applying this approach to the design and fabrication of an underwater batoid‐inspired soft robot, significant swimming performance improvements is demonstrated. An optimized composite prototype displays 50% faster swimming speeds, 28% faster turning rates, and 55% smaller turning radii than un‐optimized benchmark prototypes. Abstract : Herein a novel approach that uses topology optimization and extrusion‐based additive manufacturing with hyperelastic materials to design and fabricate bespoke composite structures for soft robots is presented. The design and fabrication of advanced composite fins for a batoid‐inspired soft robot leads to a significant improvement of swimming capabilities over traditional isotropic fins.